2017
DOI: 10.1186/s12903-017-0406-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic diversity and phenotypic traits of Streptococcus mutans isolates and their relation to severity of early childhood caries

Abstract: BackgroundEarly childhood caries (ECC) is an aggressive condition that can affect teeth of young children. This study aimed to evaluate genotypic diversity and phenotypic traits of S. mutans isolated from dental biofilms of children with different caries status in comparison with caries free (CF) children.Methods Streptococcus mutans strains were isolated from supragingival biofilm samples of CF, ECC and severe-ECC (S-ECC) children and genotyped by arbitrary-primer polymerase chain reaction - AP-PCR. S. mutans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
5
28
1
Order By: Relevance
“…The medium at 0 (T0) and 60 minutes (T60) was collected and spread with BHI plates. The number of bacteria CFU was calculated after anaerobic incubation of the BHI plate for 48 hours as detailed previously (22,42,43). Bacteria viability at each time point was expressed as the percentage of bacterial growth in relation to T 0 (100%).…”
Section: Growth Condition Of Clinical Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium at 0 (T0) and 60 minutes (T60) was collected and spread with BHI plates. The number of bacteria CFU was calculated after anaerobic incubation of the BHI plate for 48 hours as detailed previously (22,42,43). Bacteria viability at each time point was expressed as the percentage of bacterial growth in relation to T 0 (100%).…”
Section: Growth Condition Of Clinical Strainsmentioning
confidence: 99%
“…It was reported that clinical isolates of S. mutans have different cariogenic properties (16). Strains derived from SECC exhibited cariogenic traits and di cult to remove (22). It is not clear whether curcumin has effect on the S. mutans isolated from SECC.…”
Section: Introductionmentioning
confidence: 99%
“…In the same research field, Valdez et al, 428 while looking at genotypic diversity and phenotypic traits of S mutans isolates and their relation to severity of early childhood caries, concluded that "although genotypic diversity was similar in children, regardless of caries status, S mutans genotypes from caries-active children were more acid-tolerant and presented higher ability to form biofilm than those isolated from caries-free children. Acid tolerance seems to be the most important S mutans trait related to the pathogenesis of severe early childhood caries.…”
Section: Xylitol and Other Preventive Agentsmentioning
confidence: 99%
“…In addition, S. mutans genotypes from caries-active children were found more acid tolerant and presented higher ability to form biofilms than those isolated from caries-free children. The most important S. mutans trait related to the pathogenesis of sECC is thought to be tolerance to acid [39].…”
Section: Cariogenic Microorganismsmentioning
confidence: 99%